222k views
1 vote
Can you solve Please ASAP!

Can you solve Please ASAP!-example-1

1 Answer

3 votes

Answer:

x = 7/12

Explanation:

Write the expression in exponential form with the base of 2


2x^(3x-3) =
32^(3x-2)


2^(3x-3) =
2^(15x-10)

Since the bases are the same, set the exponents equal

x - 3 = 15 - 10

Move variable to the left-hand side and change its sign

3x - 15x - 3 = -10

Move constant the the right-hand side and change its sign

3x - 15x = -10 + 3

Collect like terms

-12x = -10 + 3

Calculate the sum

-12x = -7

Divide both sides o the equation by -12

x = 7/12

Solution

7/12

Alternate form

x = 0.583

User TalMihr
by
4.2k points